SIKAP KONSUMEN TERHADAP SEPEDA MOTOR YAMAHA MIO PADA PT. SABANG RAYA MOTOR DI KOTA JAMBI (CONSUMER ATTITUDE TOWARD MIO MITAC MOTORCYLE AT PT. SABANG RAYA MOTOR IN CITY JAMBI ) - Muhammad Robin (DIGEST MARKETING, 2012)
Matic motorcyle, namely Yamaha Mio (YM) has been used massively including inJambi so many firms sell itu to the coustomers. One of the firms is PT. SabangRaya. The research purpose is to analysis the customer attitude ove YM. Surveyhass benn conduct to carry out the research an the amount of sample size is 100 units.The analysis used mean to describe some atribute of customer attitiude. The resultlshows that all the atributes belong to good measurement over the YM.Keywords: Customer atttitude, Yamaha Mio, and Customer attitude.